To Climate Change, Food Security and International Migration Nexus in West Africa: A Multilevel Logistic Regression Analysis for the Gambia - Ceesay, Ebrima; Ndiaye, Mohamed Ben Omar; Mirzabaev, Alisher; Beye, Assane (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
Abstract Environmental migration is a growing concern in Africa. In this article we examine the interaction between climate change, food security and international migration in the rural Gambia using household-level data. We interacted food security and climate change, food security and remittance received and climate change and remittance received on the odds of international movement. To estimate the model, we used multilevel version of conversional logistic regression model. Further from our findings, we revealed that the typical international migrant from the rural Gambia comes from larger households size, with married person, and male-headed households and in which few members can read and write. Migrants were mostly employed as farmers before they migrated. Finally, the results from interaction terms indicated that the effect of drought, remittance received and changes in rainfall on the probability of migration in the rural Gambia is strongly positive while the effect of flood, salt intrusion and changes in temperature is strongly negative.